Effects of vitamin E administration on serum lipid profile in diabetic patients: a grade-assessed systematic review and dose–response meta-analysis of RCTs - Mehdi Karimi; Mohammad Amin Karimi; Farzad Fayedeh; Fatemeh Ziyafati Kafi; Kimia Kazemi; Sharareh Jahangiri; Omid Asbaghi (Diabetology & Metabolic Syndrome)
Abstract Background Diabetes is often associated with dyslipidemia, increasing the risk of cardiovascular complications. Studies have shown that Vitamin E, as a potent antioxidant, may improve serum lipid profile by reducing oxidative stress and inflammation. However, findings on its effects on diabetic patients remain inconsistent. To address this gap, this meta-analysis aims to evaluate the impact of vitamin E on serum lipid parameters in individuals with diabetes. Methods A search was conducted on databases from inception to June 2025 to identify relevant randomized controlled trials (RCTs). Pooled effect sizes were estimated using weighted mean differences (WMDs) with 95% confidence intervals (CIs), applying a random-effects model. All statistical analyses were performed using STATA (V. 11.2). Results The pooled analysis of 28 RCTs found that overall vitamin E administration in diabetic patients significantly reduced total cholesterol (TC) (WMD: − 5.20 mg/dL, 95% CI: [− 7.60, − 2.80], p < 0.001) and low-density lipoprotein cholesterol (LDL-C) (WMD: − 4.21 mg/dL, 95% CI: [− 7.32, − 1.09], p = 0.008). While no significant change was observed in triglyceride (TG) (WMD: − 6.19 mg/dL, 95% CI: [− 13.13, 0.75], p = 0.081) and high-density lipoprotein cholesterol (HDL-C) serum levels (WMD: 0.57 mg/dL, 95%CI: [− 0.11, 1.24], p = 0.99). Subgroup analysis showed that vitamin E reduced TG with longer durations, lowered TC and LDL-C in participants with high baseline levels, higher doses, or longer interventions, and increased HDL-C only in studies lasting over 8 weeks. Linear regression analysis found no significant associations between vitamin E dose or duration and serum lipids. In contrast, non-linear dose–response analysis showed a significant inverse relationship between vitamin E dose and TC levels. Conclusion Vitamin E administration may improve lipid profiles in diabetic patients, with significant reductions in TC and LDL-C, while effects on TG and HDL-C were not statistically significant but showed potential clinical relevance. Subgroup analysis highlighted greater benefits with higher doses (> 400 IU/day) and longer intervention durations (> 8 weeks), particularly in individuals with elevated baseline lipid levels. Further large-scale studies are needed to confirm these findings and establish optimal dosing strategies for clinical application.